Analysis of Adolescent Sexual Behavior in Bogor Taruna Terpadu Borcess Middle School (Association of Public Health Scholars based in Faculty of Public Health, Sriwijaya University, 2020)
Adolescents At This Time Experienced A Very Rapid Social Change From Traditional Society Towards Modern Society, Which In Turn Changed The Values, Norms, Including The Lifestyle Of Adolescents. The occurrence of sexual behavior in adolescents has increased which is influenced by factors from adolescent individuals and factors outside of adolescents themselves. This Study Aims To Analyze The Factors of Sexual Behavior In Adolescents. This study used a cross-sectional approach with a sample of 73 grade VIII students in Bogor Tarcess Integrated Junior High School taken by stratified random sampling, which was analyzed using the chi-square test. The results of this study were measured using a questionnaire that described sexual behavior in adolescents had occurred a lot due to factors within and outside elements of adolescent individuals, where access to information, distance, costs, parental relationships, peer influence has a p-value <α (0.05) which means that there is a relationship with risky sexual behavior in adolescents. Still, the attitude factor shows different results ie, 0.853> α (0.05 ), which means not related. Parents and Schools need to work together in providing reproductive health education to adolescents to avoid sexual behavior.